Outsourcing accountability: Extractive data practice and inequities of power in humanitarian third-party monitoring - Stephanie Diepeveen; John Bryant; Mahad Wasuge (Big Data & Society)
Since the early 2010s, humanitarian donors have increasingly contracted private firms to monitor and evaluate humanitarian activities, accompanied by a promise of improving accountability through their data and data analytics. This article contributes to scholarship on data practices in the humanitarian sector by interrogating the implications of this new set of actors on humanitarian accountability relations. Drawing on insights from 60 interviews with humanitarian donors, implementing agencies, third-party monitors and data enumerators in Somalia, this article interrogates data narratives and data practices around third-party monitoring. We find that, while humanitarian donors are highly aware of challenges to accountability within the sector, there is a less critical view of data challenges and limitations by these external firms. This fuels donor optimism about third-party monitoring data, while obscuring the ways that third-party monitoring data practices are complicating accountability relations in practice. Resultant data practices, which are aimed at separating data from the people involved, reproduce power asymmetries around the well-being and expertise of the Global North versus Global South. This challenges accountability to donors and to crisis-affected communities, by providing a partial view of reality that is, at the same time, assumed to be reflective of crisis-affected communities’ experiences. This article contributes to critical data studies by showing how monitoring data practices intended to improve accountability relations are imbued with, and reproduce, power asymmetries that silence local actors.